INFLUENCE STYLE LEADERSHIP AND MOTIVATION WORK TO PERFORMANCE EMPLOYEE - Jimmy Carter; Lita Norfiana (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Goal study This For now influence style leadership and motivation Work in a way partial and simultaneous to performance employee Central Kalimantan provincial DPRD secretariat office . Population in study This is employee office Central Kalimantan Province DPRD Secretariat . Sample in study This employee office Central Kalimantan DPRD secretariat , totaling 61 employees Based on the results of the tests carried out, the leadership style variable partially shows that there is a significant influence on employee performance variables. The work motivation variable partially shows that there is a significant influence on the employee performance variable, and the two independent variables, namely leadership style and work motivation together (simultaneously) have an effect on the employee performance variable. Keywords : _ Leadership Style , Motivation and Performance Employee